Knowledge management and its impact on achieving sustainable competitive advantage - an exploratory study of the opinions of a sample of Zain Telecommunications Company managers - Ahmed Abdullah Amanah Shammari, (Iraqi Journal for Administrative Sciences, 2025)
This Research aimed at determining the influence of Knowledge Management on the Achieving Sustainable Competitive Advantage of Iraqi Organizations. For this purpose the researcher has depended on the dimensions/Processes of Knowledge Management (Knowledge Generating, Knowledge Storage, Knowledge Distribution, Knowledge Application) according to (Goldoni&Oliveira,2010:302). The dimensions of Sustainable Competitive Advantage (Value, Rarity, Inimitability, Non-Substitutability) that have been used are according to (Johnson,etal.,2012:54). The Zain Company for Communications has been chosen to verify this Research via a questionnaire used (30) individuals of the managers of the company , in addition to personal interviews. The Spearman connection factor , and the (t) test to recognize the identity of this relation, and the (F) test to determine the identity of the regression equation , also the (R 2 ) has been used to explain the degree of the influence of the independent variable in the dependent variable . Some of the most important conclusions the study arrived at are that Knowledge Management have a significant impact in achieving Sustainable Competitive Advantage. The study has been concluded with a number of recommendations ,some of which are :  Analyzing capabilities and recourse in the company by VRIN in a wider scope in the light of changing technology environment which is characterized by highly level of competition.  Consolidating the talent human resources and capabilities they have high level of expertise to Innovation and creative in company.  Keeping a high level of new technologies that allow company to provide new service that giving value to its customers, in a way that achieve Sustainable Competitive Advantage.